L’art du portrait entre l’esthétique occidentale et persane dans l’Iran safavide 1501-1736 - Aya Sakkal (Recherches Germaniques)
The presentation focuses on the opening of the Safavid dynasty from the 16th to the 18th century to Western painting, encouraging the arrival of Western painters with their own conceptions of art and their personal techniques. The study highlights the impact of Western pictorial on Iranian art with the introduction of the techniques of the Renaissance such as perspective, shadow, light as well as the adoption of the Western-style art of the portrait. This innovative current joined a social phenomenon where successive shahs, their courts as well as individuals from the society’s upper echelons, showed an unprecedented craze to be portrayed in Western style. The study emphasizes also the resistance movement at the head of which are the great masters of Persian miniature. Those perpetuated the aesthetics tradition and condemned the art of portraying the living and advocated at the same time for the defense of the values of the art of illustrating fictional tests and oriental style portrait. Finally, the study analyzes the work of numbers of painters who adapted pictorial novelties as a synthesis between tradition and innovation making it legal, from a religious point of view, to borrow from Western imagery by creating an intermediate, yet a new form of art.